3D-printed artificial bone scaffolds: the design of materials, the incorporation of bioactive substances, and the integration of vascularized tissue flaps - Duan, Qida; Shao, Hongyun; Luo, Ning; Wang, Fuyang; Cheng, Liangliang; Ying, Jiawei; Zhao, Dewei (Frontiers in Bioengineering and Biotechnology, 2025)
With the advancements in tissue engineering, materials science, microsurgery, and the maturation of 3D printing technology, 3D-printed artificial bone scaffolds have provided an innovative strategy that integrates structural bionics and functional synergy for the treatment of large-segment bone defects. Compared with conventional bone grafting, this technology not only precisely reconstructs anatomical geometry and promotes cell migration through porous design, but also, via surface modification, enables accurate loading and controlled release of multiple bioactive factors, thereby actively regulating osteogenesis and angiogenesis, enhancing regeneration efficiency, and overcoming the traditional scaffold limitation of “mechanical support only, lack of biological guidance.” Nevertheless, repair of large-segment defects still faces challenges such as early ischemia, restricted nutrient diffusion, and slow callus formation. To address this bottleneck, the present study summarizes a “vascularization-osteogenesis integration” scaffold design paradigm that combines 3D printing with vascularized bone substitutes, realizing a “scaffold plus vascular-pedicled flap” co-implantation strategy; the vascular network of the flap traverses the entire scaffold, establishing a co-culture microenvironment of endothelial cells and mesenchymal stem cells and maximizing osteogenic and angiogenic efficiency. This review systematically analyzes the biomaterial properties of various 3D-printed bone scaffolds, strategies for loading bioactive factors, and cutting-edge progress in pedicled flap transplantation for bone and vessel regeneration, highlighting their distinctive advantages in vascularization and bioactivity modulation over traditional bone grafting, aiming to promote a paradigm shift from “structural replacement” to “biological function reconstruction” and provide both theoretical innovation and practical guidance for accelerating clinical translation of bone tissue engineering.